Successful Practices of Leadership in School Reform: A Case Study in a Private School in Dubai - Abouelanein, Ahmed (2020)
Abstract Education reform is the remedy nations seek to develop and compete in a rapidly growing world. Different approaches to school reform, the main field of education, vary according to the contextual circumstances. However, leadership practices have the pivotal role that determines the success or failure of any school reform. Therefore, this study investigates how school reform has been successful due to successful leadership practices to provide recommendations of the best practices. The study was designed to benefit from the mixed method that helps reach the best understanding of the research context. A questionnaire was developed to collect quantitative data to understand the perspectives of teachers and school leadership on school reform. In addition, qualitative data was collected from a semi-structured interview with school leadership members to identify practices of leadership that led to school reform. Data analysis showed that both teachers and leadership members defined school reform as a change in teaching and learning and school discipline approaches, teacher-parent involvement in curriculum design, and an effective parents’ engagement in their children’s learning. Moreover, the study concluded that the best practices for school reform included: conducting evidence-based professional development, encouraging collaborative decision-making among all stakeholders, and developing in-and-out school healthy relationships. It is evident from the study findings that although school reform is designed and steered by school leadership members, all stakeholders have their prominent shares especially teachers and parents.